LITERATURE REVIEW : PELEPASAN INFORMASI MEDIS KEPADA PIHAK ASURANSI - Almas Ummi Fatharina; Sri Sugiarsi; Trismianto Asmo Sutrisno (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2021)
Abstract Release of medical information must be subject to applicable procedures and must be with the patient's consent. Patients must make a stamped written statement that has authorized a third party to request medical data from a doctor. The purpose of this study is to determine the policy of releasing medical information and the flow of procedures for releasing medical information to the insurer. The research method in this study is to use a literature review design, namely research that examines research articles on the release of medical information to insurance parties by comparing, summarizing, and drawing conclusions. The search strategy used keywords and operator bundles used in this study, namely